2022
DOI: 10.1111/ijac.14099
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of zinc oxide/selenium composite for UV blocker application

Abstract: Development of reliable ultraviolet (UV) blockers is crucial for UV radiation protection applications such as sunscreen and UV‐resistant fabric. To date, zinc oxide (ZnO) has been extensively used as a physical UV blocker worldwide but has also been criticized for with its unfavored UV‐induced reactive oxygen species (ROS) generation phenomena. As an attempt to suppress the photocatalytic activity of ZnO without compromising its UV absorbance property, amorphous selenium (Se) nanoparticles (NPs) were incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Zinc oxide has been extensively utilized worldwide as a physical blocker against UV radiation, despite its mostly criticized UV-induced reactive oxygen species (ROS) generation phenomena. This phenomenon occurs due to the creation of photoinduced charge carriers in ZnO from solar photons with energies higher than 3.37 eV (wavelength shorter than 368 nm), which interact with oxygen and water molecules on the surface of nanoparticles . In addition to its UV-blocking abilities, research has demonstrated that zinc oxide can directly protect plants from diseases such as pearl millet downy mildew .…”
Section: Resultsmentioning
confidence: 99%
“…Zinc oxide has been extensively utilized worldwide as a physical blocker against UV radiation, despite its mostly criticized UV-induced reactive oxygen species (ROS) generation phenomena. This phenomenon occurs due to the creation of photoinduced charge carriers in ZnO from solar photons with energies higher than 3.37 eV (wavelength shorter than 368 nm), which interact with oxygen and water molecules on the surface of nanoparticles . In addition to its UV-blocking abilities, research has demonstrated that zinc oxide can directly protect plants from diseases such as pearl millet downy mildew .…”
Section: Resultsmentioning
confidence: 99%
“…The quest for enhancing the UV-barrier properties of PLA has spurred the development of innovative methods. One avenue involves the incorporation of UV-blocking additives during the manufacturing process, effectively reducing the penetration of harmful UV radiation [6]. Another approach entails the design of multilayer packaging structures, where a dedicated UV-blocking layer adds an extra layer of protection.…”
Section: Introductionmentioning
confidence: 99%